Light excess stimulates Poly-beta-hydroxybutyrate yield in a mangrove-isolated strain of Synechocystis sp. (January 2021) - Gracioso, Louise Hase; Bellan, Alessandra; Karolski, Bruno; Cardoso, Letícia Oliveira Bispo; Perpetuo, Elen Aquino; Nascimento, Claudio Augusto Oller do; Giudici, Reinaldo; Pizzocchero, Valentino; Basaglia, Marina; Morosinotto, Tomas
Highlights: A cyanobacterium (B12) isolated from a contaminated area was shown to produce PHB. Strain B12 showed high biomass production under a high-intensity illumination. High light intensities also strongly stimulated PHB accumulation. PHB productivity is competitive with best producing strains reported in literature. Abstract: Poly-β-hydroxybutyrate (PHB) is a biodegradable biopolymer that may replace fossil-based plastics reducing its negative environmental impact. One highly sustainable strategy to produce these biopolymers is the exploitation of photosynthetic microorganisms that use sunlight and CO2 to produce biomass and subsequently, PHB. Exploring environmental biological diversity is a powerful tool to find resilient microorganisms potentially exploitable to produce bioproducts. In this work, a cyanobacterium ( Synechocystis sp.) isolated from a contaminated area close to an important industrial complex was shown to produce PHB under different culture conditions. Carbon, nutrients supply and light intensity impact on biomass and PHB productivity were assessed, showing that the highest yield of PHB achieved was 241 mg L −1 (31%dcw ) under high light intensity. Remarkably this condition not only stimulated PHB accumulation by 70% compared to other conditions tested but also high cellular duplication rate, maximizing the potential of this strain for PHB production.